Lipid dynamics and trophic patterns in Pleuragramma antarctica life stages. Issue 5 (18th March 2015) - Giraldo, Carolina; Mayzaud, Patrick; Tavernier, Eric; Boutoute, Marc; Penot, Florian; Koubbi, Philippe
Abstract: The aim of this study was to clarify the trophic patterns of the key species Pleuragramma antarctica in the Dumont d'Urville Sea, through its development and possible changes according to sampling locations. Variability in diet composition of larvae, juvenile and adult P. antarctica was analysed using fatty acid markers. Analysis of lipid class in P. antarctica reflected lipid accumulation with increasing size at all sampling stations. The fatty acid composition of triacylglycerol highlighted ontogenetic changes in the diet. Phytoplankton markers, such as C16PUFA:C16 and EPA:DHA ratios >1, and carnivorous markers in larvae suggested an omnivorous diet. Comparison between the fatty acid signature of P. antarctica older stages (juveniles and adults) and zooplankton species using OPLS-discriminant analysis indicated that juveniles fed mainly on euphausiid larvae and to a minor extent on copepods, and confirmed that non-herbivorous copepods were the main prey for adults. Our results suggest that different feeding patterns and a generalist strategy in P. antarctica with juveniles feeding on bigger prey than adults, probably as a result of prey availability according to their vertical segregation pattern.